Cross-equatorial flow through an abyssal channel under the complete Coriolis force: Two-dimensional solutions - Stewart, A; Dellar, P (2011)
The component of the Coriolis force due to the locally horizontal component of the Earth's rotation vector is commonly neglected, under the so-called traditional approximation. We investigate the role of this " non-traditional" component of the Coriolis force in cross-equatorial flow of abyssal ocean currents. We focus on the Antarctic Bottom Water (AABW), which crosses from the southern to the northern hemisphere through the Ceara abyssal plain in the western Atlantic ocean. The bathymetry in this region resembles a northwestward channel, connecting the Brazil Basin in the south to the Guyana Basin in the north. South of the equator, the AABW leans against the western continental rise, consistent with a northward flow in approximate geostrophic balance. The AABW then crosses to the other side of the abyssal channel as it crosses the equator, and flows into the northern hemisphere leaning towards the east against the Mid-Atlantic Ridge.The non-traditional component of the Coriolis force is strongest close to the equator. The traditional component vanishes at the equator, being proportional to the locally vertical component of the Earth's rotation vector. The weak stratification of the abyssal ocean, and subsequent small internal deformation radius, defines a relatively short characteristic horizontal lengthscale that tends to make non-traditional effects more prominent. Additionally, the steep gradients of the channel bathymetry induce large vertical velocities, which are linked to zonal accelerations by the non-traditional components of the Coriolis force. We therefore expect non-traditional effects to play a substantial role in cross-equatorial transport of the AABW.We present asymptotic steady solutions for non-traditional shallow water flow through an idealised abyssal channel, oriented at an oblique angle to the equator. The current enters from the south, leaning up against the western side of the channel in approximate geostrophic balance, and crosses the channel as it crosses the equator. The " non-traditional" contribution to the planetary angular momentum must be balanced by stronger westward flow in the channel, which leads to an increased transport in a northwestward channel, and a reduced transport in a northeastward channel. Our results suggest that as much as 10-30% of the cross-equatorial flow of the AABW may be attributed to the non-traditional components of the Coriolis force. © 2011 Elsevier Ltd.